2018
DOI: 10.3138/cmlr.4051
|View full text |Cite
|
Sign up to set email alerts
|

Task-Based Teaching of Indigenous Languages: Investment and Methodological Principles in Macuiltianguis Zapotec and Salish Qlispe Revitalization

Abstract: Task-based language teaching (TBLT) is a pedagogical approach that involves identifying real-world tasks that learners need to be able to do in the target language and then developing classroom-appropriate, context-specific versions of these tasks. In this paper, we use Long’s methodological principles for TBLT to evaluate a task-based approach within two Indigenous language-teaching contexts: the Macuiltianguis Zapotec classroom in Oaxaca, Mexico, and a workshop for teachers of Salish Qlipse in the state of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…These findings are in line with previous research on task-based (Ellis, 2003;Riestenberg & Sherris, 2018) and student-centered approaches to language learning. Although the creation of the book was not itself task-based, it was linked to a task-based activity; perhaps the success of the student-generated book was furthered by completion of the task-based hiking activity which reinforced what the book introduced.…”
Section: Resultssupporting
confidence: 92%
“…These findings are in line with previous research on task-based (Ellis, 2003;Riestenberg & Sherris, 2018) and student-centered approaches to language learning. Although the creation of the book was not itself task-based, it was linked to a task-based activity; perhaps the success of the student-generated book was furthered by completion of the task-based hiking activity which reinforced what the book introduced.…”
Section: Resultssupporting
confidence: 92%
“…Ideology refers to attitudes, beliefs and values towards language teaching, learning and use. If a language-revitalization project is to be successful, it needs to work within a community to identify and shift linguistic ideologies (Riestenberg & Sherris, 2018). In a study of immersion students in Québec, Ballinger (2017) found that the status of the language at an individual, classroom and societal level impacted student's minority language use and investment.…”
Section: Identity As Investmentmentioning
confidence: 99%
“…TBLT focuses on discovering real situations where the LLs are likely to speak the target language and then developing class activities around those contexts and situations. Riestenberg and Sherris (2018) found that TBLT was an effective teaching strategy for Macuiltianguis Zapotec and Salish Qlipse, indigenous languages spoken in Mexico and the United States, respectively. One advantage this pedagogy has over other methods is that it is based on communicative needs rather than linguistic structure, meaning there is little reliance on textbooks or grammars, two resources which are often lacking in indigenous language contexts.…”
Section: L2 Teaching and Pedagogymentioning
confidence: 98%
“…Another language teaching strategy employed in an indigenous context is Task Based Language Teaching (TBLT; Riestenberg & Sherris, 2018). TBLT focuses on discovering real situations where the LLs are likely to speak the target language and then developing class activities around those contexts and situations.…”
Section: L2 Teaching and Pedagogymentioning
confidence: 99%